The hybrid method for the plate-finned tube evaporator design process - Starace Giuseppe (EDP Sciences, 2021)
The plate-finned tube evaporator performance, in terms of heat transfer rate and refrigerant pressure drops, is influenced by several choices done during the design process to be carried out complying with different constraints. In this paper different refrigerant circuitry layout options together with other parameters variations were investigated with the purpose of supporting designers. Performance predictions were calculated using the hybrid method as well as appropriate Performance Evaluation Criteria (PEC) were adopted to select the best layout. The hybrid method has been here revised and improved aiming at modelling heat exchangers with an approach closer to real configurations that include complex circuit layouts. The method was chosen as its main advantage (high accuracy in the results with low computational costs) allowed to easily perform operating conditions modifications to be compared.